Sharing cells with Wolbachia: the transovarian vertical transmission of Culex pipiens densovirus. (21st January 2019) - Altinli, Mine; Soms, Julien; Ravallec, Marc; Justy, Fabienne; Bonneau, Manon; Weill, Mylene; Gosselin‐Grenet, Anne‐Sophie; Sicard, Mathieu
Summary: Culex pipiens densovirus (CpDV), a single stranded DNA virus, has been isolated from Culex pipiens mosquitoes but differs from other mosquito densoviruses in terms of genome structure and sequence identity. Its transmission from host to host, the nature of its interactions with both its host and host's endosymbiotic bacteria Wolbachia are not known. Here, we report the presence of CpDV in the ovaries and eggs of Cx. pipiens mosquitoes in close encounters with Wolbachia . In the ovaries, CpDV amount significantly differed between mosquito lines harbouring different strains of Wolbachia and these differences were not linked to variations in Wolbachia densities. CpDV was vertically transmitted in all laboratory lines to 17%–20% of the offspring. For some females, however, the vertical transmission reached 90%. Antibiotic treatment that cured the host from Wolbachia significantly decreased both CpDV quantity and vertical transmission suggesting an impact of host microbiota, including Wolbachia, on CpDV transmission. Overall our results show that CpDV is transmitted vertically via transovarian path along with Wolbachia with which it shares the same cells. Our results are primordial to understand the dynamics of densovirus infection, their persistence and spread in populations considering their potential use in the regulation of mosquito vector populations.